2018
DOI: 10.1186/s40780-018-0125-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug-related problems detected by routine pharmaceutical interventions: safety and economic contributions made by hospital pharmacists in Japan

Abstract: BackgroundPharmaceutical intervention enables safe and effective pharmacotherapy by avoiding of adverse drug reactions (ADRs) and efficacy attenuations. Many prescriptions require optimization, and pharmaceutical interventions are inextricably associated with the prevention of potential drug-related problems (DRPs). Although the analysis and understanding of pharmaceutical interventions can lead to improvement in prescription, the analysis of routine pharmaceutical interventions in Japan in insufficient. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 31 publications
1
42
1
1
Order By: Relevance
“…ICU physicians might feel pressure when they held different opinions on treatment plans, and unnecessary medication orders could be carried out in this way. These situations bring great opportunities for pharmacists to get involved, communicate with both sides and ensure medication safety (Rudis and Brandl, 2000;Kane et al, 2003;Penm et al, 2014a;Tasaka et al, 2018;Reinau et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICU physicians might feel pressure when they held different opinions on treatment plans, and unnecessary medication orders could be carried out in this way. These situations bring great opportunities for pharmacists to get involved, communicate with both sides and ensure medication safety (Rudis and Brandl, 2000;Kane et al, 2003;Penm et al, 2014a;Tasaka et al, 2018;Reinau et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Patients admitted to the intensive care unit (ICU) are at higher risk for developing DRPs, from 2.1/1,000 to 804.5/1,000 patients days (Garrouste-Orgeas et al, 2010;Garrouste-Orgeas et al, 2015;Garrouste-Orgeas et al, 2016), primarily cause by their critical diseases status or complications, the use of various high alert medications, and the rapid changing pharmacotherapies (Kari et al, 2018). Previous studies have shown that critical care pharmacists can play an essential role in promoting the delivery of pharmaceutical care (PC) and improve the overall quality of health care by offering individualized recommendations in complicated drug regimens, reducing the incidence rate of DRPs, and decreasing preventable ADEs (Tasaka et al, 2018;Lee et al, 2019;Reinau et al, 2019). However, the development of PC in the ICU is currently facing three major challenges worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…They are considered adverse events and occur in patients at all levels of healthcare, whether home care, 2 institutional long term care, 3 community pharmacy 4 or hospital. 5 In the hospital setting, incidence rates of DRP have been reported for specific patient populations, with high incidence rates in children 6 and the elderly, 7 as well as in certain clinical specialties such as cardiology, 8 neurology 9 and surgery. 7 This high incidence of DRP negatively affects the quality of life of the patient and increases the economic and social burden of illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…7 This high incidence of DRP negatively affects the quality of life of the patient and increases the economic and social burden of illnesses. 5 Many of the admissions to emergency departments, 10 11 many causes of extended hospital stays 12 or of patient re-admissions, 13 and even of deaths, are due to a DRP. It has been reported that these negative outcomes are proportional to the complexity of the drug use process, 14 with some of the described risk factors being polypharmacy, hepatopathies, nephropathies and the use of high-risk medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Podobnie jak w badaniu, 62letnia pacjentka dzięki interwencji zakończyła terapię sulpiry dem, co pozwoliło na redukcję jej dotychczaso wych kosztów leczenia [8].…”
Section: Tom 75 • Nr 9 • 2019unclassified